The Influence of Social, Political, and Social Media on COVID-19 Risk Communication and Health Behaviour in Thailand - Termmee, Suphunnika (Technium Social Sciences Journal, 2023)
To combat the impact of COVID-19, the Thai government recognized the importance of effective risk communication as a means of disease control and prevention. However, due to the unprecedented nature of the pandemic, executing flawless risk communication was challenging. This research aims to explore and evaluate the critical factors that influence the communication and perception of risks. The purpose of this study is to assist the government in developing effective policies for future risk communication and understand the public's health protection behaviors. By analyzing qualitative data through qualitative methodology and the use of the NVIVO program, the study determined that social media and social/political factors significantly affect an individual’s understanding and health protection behavior. Social factors show that people tend to behave similarly and believe information based on their surroundings, including family, friends, colleagues and others. Politically, individuals who trust the current government follow information from official sources except daily numbers of COVID-19 patients. Those who do not trust the government seek information from other sources, especially online channels, and tend to believe information sent by opposing parties. Regardless of information exposure, individuals implement health protection behaviors in high level such as mask-wearing, vaccination and hygiene.